Bound state solution of schrodinger equation with modified Hylleraas plus inversely quadratic potential using parametric Nikiforov-Uvarov method - Mohammed, Imrana Habibat; Yabagi, Jibrin Alhaji; Akusu, Patrick Ovie; Ubaidullah, Ahmad; Ladan, Muhammad Bello; Babakacha, Ndanusa (Journal of Physics: Theories and Applications, 2024)
In this work, an approximate bound state solution to Schrodinger equation with modified Hylleraas plus inversely quadratic potential was obtained using the parametric form of the Nikiforov-Uvarov method. Applying the elegant approximation to deal with the centrifugal term for arbitrary orbital angular quantum number, the energy spectrum and the corresponding wave function was obtained.